(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A smartphone is said to be an extension of a mobile user’s oneself. It is the ultimate mobile device today for humans, the one device that humans cannot avoid using, leave behind when on the move and becomes a necessity to own one. It allows humans to communicate and perform many daily personal tasks. Smartphones continue to evolve embedding advanced device technologies, sophisticated processes and applications. This symbiotic combination generates immense data on a temporal and spatial scale for a mobile user. These data represent the behaviors of a mobile user, which is unique. In the digital mobile realm, there exists some digital identity about a mobile user, what can be thought as the mobile user’s digital pheromone. This data mining study uses Android Device Analyzer dataset consists of Battery Level, Battery Temperature, Battery Volt and App variables to understand the levels of volatility and their correlation measures. The finding shows there are wide dispersions for Battery Level, Battery Temp, Battery Volt and no statistical relationship exists for Battery Volt/App and Battery Temp/App correlation. Using a simple inequality that only a limited number of mobile users are contained within one standard deviation from the population mean, a smaller set of users exists. The results show that ‘uniqueness’ percentage of a mobile user increased from 61.7% and 66.7% for single variable to 81.7% in multi-variate condition, to 100% using the simple inequality. Ultimately, this uniqueness indicates that a mobile user can have a unique identity, in the digital mobile world from the daily mobile data generated.